Алое платье: [повесть : для среднего школьного возраста] / Гордиенко Г. - Гордиенко Галина Анатольевна (Чинар, 2021)
Экземпляры: БС (20220414) / Инвентарный номер: РТШ55164 / Сис.шифр: 84(2) / Авт.знак: Г 68 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-4